An Upper bound on the Error Exponent in Lossless Source Coding with a Helper - Kang, Wei; Liu, Nan (2018 IEEE Information Theory Workshop (ITW), 2018)
In this paper, we study the error exponent in the problem of lossless source coding with a helper. We use the inherently typical subset lemma to remove the Markov chain constraint in the proof of the converse and obtain an upper bound on the error exponent, which is very close to the existing lower bound. The proposed upper bound and the existing lower bound meet when the rate pair is close to the boundary of the optimal rate region.